Implementing social security programmes in post-conflict Iraqi Kurdistan region: the case of "Social safety net" and "Rights and privileges to families of martyrs and genocide survivors" after 2001 - Irwani, Muslih (2014)
By drawing on the hegemony of politics over the administration and social policy in the Kurdistan Region, researching the implementation of social security programmes is critically important for understanding the outlook of the Kurdistan Regional Government (KRG) towards social policy. This research broadly examines policy implementation theories within the context of this politically underdeveloped region, taking into account the social security programmes of the KRG as a case study. Primary questions could be asked here, such as what are the critical factors in the implementation of social security in the KRG? Why has the KRG not adopted and implemented an effective social policy with its developmental programmes since its relative economic growth in 2001? My focused question in the current research is: why has the KRG implemented its two main social cash transfers (‘Rights and Privileges to Families of Martyrs and Genocide Survivors’ and ‘Social Safety Net’) differently? Exploring these cases would favour understanding of the extent to which the political conditions of the Kurdistan Region have influenced the implementation of social benefit schemes of the KRG. Experiencing its national struggle in the past, intra-Kurdish civil war during the 1990s and partisanship afterwards has formed the KRG.